Study on electric spark discharge between pantograph and catenary in electrified railway - Hongyi Zhou; Fuchuan Duan; Zhigang Liu; Long Chen; Yang Song; Yexin Zhang (IET Electrical Systems in Transportation)
Abstract The electric spark caused by pantograph‐catenary (PC) electrical contact failure happens frequently, it is a kind of arcing phenomenon which can severely affect the current collection of PC. The theoretical analysis and modelling of PC electric spark are tried. First, the contact spots between PC and their temperature rise are analysed and derived based on the classical electrical contact theory, respectively. The mechanism of spark discharge is revealed through the analysis of PC voltage difference, and the spark discharge model is proposed combining with the spot temperature rise formula and spark discharge mechanism. Then, in order to obtain some key parameters in an electric spark discharge model, such as contact force and contact current, the structure model of PC and the circuit model of vehicle‐grid are established for the calculation of the spark rate in PC. Finally, the spark rate is calculated and analysed under the different parameters in PC system. The calculation results are verified by the experiment results. Through the presentation of the correlation of electric spark discharge and factors, such as contact force, contact current and material of PC, this study can support the assessment of electrical contact quality in the PC system in future study.